2010
DOI: 10.1007/s00167-010-1185-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in single-leg hop biomechanics following anterior cruciate ligament reconstruction

Abstract: When a patient performs a clinically normal hop test based on distance, it cannot be assumed that the biomechanics are similar between limbs. The objective was to compare takeoff and landing biomechanics between legs in patients who have undergone anterior cruciate ligament reconstruction. Kinematics and ground reaction forces were recorded as 13 patients performed the single-leg hop on each leg. Distance hopped, joint range of motion, peak joint kinetics and the peak total extensor moment were compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
165
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(192 citation statements)
references
References 25 publications
22
165
2
3
Order By: Relevance
“…While they found that a specific biomechanical profile, including increased frontal plane knee motion and increased hip transverse plane moments, predicted a second ACL injury, there was no information provided as to performance on specific RTS tests. Another study by Orishimo and colleagues (2010) reported that individuals who had been cleared for return to sport following ACLR demonstrated altered lower extremity biomechanics during both the take-off and landing of a single leg hop for distance, despite a clinically acceptable performance on the test, however the incidence of re-injury following return to sport participation was not reported [12]. Future studies are needed that evaluate both performance on RTS tests, lower extremity biomechanics, and reinjury events.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…While they found that a specific biomechanical profile, including increased frontal plane knee motion and increased hip transverse plane moments, predicted a second ACL injury, there was no information provided as to performance on specific RTS tests. Another study by Orishimo and colleagues (2010) reported that individuals who had been cleared for return to sport following ACLR demonstrated altered lower extremity biomechanics during both the take-off and landing of a single leg hop for distance, despite a clinically acceptable performance on the test, however the incidence of re-injury following return to sport participation was not reported [12]. Future studies are needed that evaluate both performance on RTS tests, lower extremity biomechanics, and reinjury events.…”
Section: Measurementmentioning
confidence: 99%
“…However, more recent guidelines suggest that performance on RTS tests must be at least 90% that of the un-involved extremity. Examples of RTS tests commonly implemented include the 5-jump test, single leg hop for distance, triple hop for distance, single leg cross over hop for distance, single leg 6 meter hop for time, or some combination of these tests [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We also wanted to supplement the work conducted by Dai et al 6 by exploring the relationship between GRF symmetry and knee power symmetry, as analysis of joint power provides insight into energy absorption during landing. 4 A significant limitation of this study is that subjects did not have a history of ACL reconstruction, which limits our ability to generalize to this population. In addition, a relatively small sample was included.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The typical pattern of asymmetry is for the uninjured knee to experience greater loading compared to the knee that underwent the ACL reconstruction. Persistent asymmetry in knee kinetics may place the athletes at risk for a second ACL injury.…”
mentioning
confidence: 99%
“…Compared to the nonsurgical side, the internal knee extensor moment on the surgical side is lower during squatting, 24 a lateral stepdown manuever, 7 stair climbing, 14 and single-leg hopping or jumping. 7,20,26 The surgical side, as compared to the nonsurgical side, also displays a lower vertical force during squatting 4,17 and the landing and take-off phases of a drop vertical jump, 21 and a higher vertical force in the landing phase of a single-leg hop. 26 Finally, the loading rate on the surgical side is lower than that of the nonsurgical side when landing from a drop vertical jump.…”
mentioning
confidence: 99%